Petrol Pumps to Power Plugs: Is the Surge in Electric Two-Wheeler Adoption in Kathmandu Due to Unstable Petroleum Prices? - Maharjan, Lasana Singh; Yuangyai, Nuttaya (International Journal of Energy Economics and Policy, 2024)
Since the dawn of the 21st century, the awareness towards environmental concern and sustainability slowly began to rise and the “Electric Wave” truly encompassed the world with electric automobiles. Nepal was no exception to this global electric wave. This research explores a key determinant behind this transition, the influence of fluctuating petroleum price. Using secondary data obtained from registrations of electric and petroleum two-wheelers at the Transport Management Office in Kathmandu, under the Ministry of Labor, Employment, and Transport as well as historical petrol prices over the past 4 years from 2019 to 2023, this research seeks to offer valuable insights into the connection between petrol prices and the adoption of electric vehicles in Kathmandu, Nepal. Using SPSS software, a linear regression analysis was conducted and it revealed that while petroleum prices played a role, they were not the sole determinant affecting adoption. This study contributes to the growing body of knowledge on sustainable transportation choices and their drivers. It provides valuable insights for policymakers, consumers, and industry stakeholders, as it underscores the influence of fuel prices on consumer choices and the potential for electric two-wheelers to become a viable alternative in the context of Kathmandu’s urban transport.